Faktor-faktor yang Memengaruhi Penghidupan Berkelanjutan (Sustainable Livelihood) Petani Pinggiran Kota Bandung - Rahman, Naufal; Saidah, Zumi; Yudha, Eka Purna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Sustainable livelihood is a condition where the community is able to deal with pressures and shocks to manage resources for the welfare of their families now and in the future. It should be noted that the concept of sustainable livelihood is in line with the concept of sustainable development, where sustainable development seeks to maintain the cultural sustainability of a community so that it remains sustainable in the future. The purpose of this study is to analyze sustainable livelihoods and the factors influencing sustainable livelihoods of farming households in the peripheral areas of Bandung City. This research uses a mixed method design of quantitative and qualitative. The research method used was the survey method. The data analysis techniques used were descriptive analysis and multiple linear regression analysis. The results show that the condition of sustainable livelihoods of farming households in the peripheral areas of Bandung City is not bad, but improvements are still needed to improve the condition. The respondents' social environment, which is still supportive in their profession as farmers, also provides a sense of comfort to farmers. Natural capital, financial capital, social capital, and human capital have a significant influence on sustainable livelihoods of farmer households in the peri-urban areas of Bandung City. Meanwhile, physical capital has no effect on the sustainable livelihood of farmer households in the peri-urban areas of Bandung City.